Implementasi Keteladanan Guru dalam membentuk Karakter Peduli Sosial dan Disiplin Siswa melalui Pendidikan Sekolah Ramah Anak pada Siswa Kelas Atas SD Muhammadiyah 16 Surakarta - Kartikasari, Farida Nur; , Dra. Risminawati, M.Pd (2017)
It is found that many Student inthe age of elementary school have lack of social care and egosentris. In the matter of discipline, most of students are also lake of discipline, for instance: coming late, inappropriate uniform, do not fulfill the given homework, etc. The purpose of this study to determine: (1) the implementation of exemplary teachers in shaping the character of social care and discipline. (2) the implementation of the Child Friendly School(3) implementation of exemplary teachers in shaping the character of social care and discipline through the Child Friendly School education at upper grade students. (4) Knowing the barriers and solutions of implementation of exemplary teachers in shaping the character of social care and discipline through the Child Friendly School education at upper grade students of SD Muhammadiyah 16 Surakarta. This type of research used is qualitative research. Methods of data collection is done through interviews, observation and documentation. The validity of the data by triangulation and triangulation methods. Interactive data analysis techniques of data collection, data reduction, data presentation and conclusion.The informants for this research consists of the headmaster, teacher of fourth and fifth grade, and the fourth and fifth grade sstudents of SD Muhammadiyah 16 Surakarta. The results of the research are : (1) teachers modelling has ran very well at SD Muhammadiyah 16 Surakarta. (2) The principle of Child Friendly School has been undergone well by fulfilling the 3P princiles (provision, protection, and participation). (3) teachers modelling related to Child Friendly School has successfully build students character of social care and discipline. (4) There are some obstacles in building students character of social care and discipline, but there are also severel attempts to overcome those obstacles. The results of this research is intended to contribute in educational system of elementary school level. Keywords : modelling, character, social care, discipline, child friendly school